2009
DOI: 10.1152/ajprenal.90438.2008
|View full text |Cite
|
Sign up to set email alerts
|

PERP, a p53 proapoptotic target, mediates apoptotic cell death in renal ischemia

Abstract: Singaravelu K, Devalaraja-Narashimha K, Lastovica B, Padanilam BJ. PERP, a p53 proapoptotic target, mediates apoptotic cell death in renal ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…Both oxidative stress and ischemia have been reported to increase the number of apoptotic cells within the kidney (20,31,39); therefore, we investigated the extent of renal cell apoptosis using the TUNEL assay on formalin-fixed kidneys. Levels of apoptosis tended to be elevated in both the servo-controlled and uncontrolled kidneys compared with kidneys from saline-infused sham rats, but did not reach levels of statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Both oxidative stress and ischemia have been reported to increase the number of apoptotic cells within the kidney (20,31,39); therefore, we investigated the extent of renal cell apoptosis using the TUNEL assay on formalin-fixed kidneys. Levels of apoptosis tended to be elevated in both the servo-controlled and uncontrolled kidneys compared with kidneys from saline-infused sham rats, but did not reach levels of statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue sections were then mounted for evaluation under Leica fluorescent microscope with appropriate filters Cell culture and hypoxic injury. Cell culture and hypoxic injury were performed as previously described (41). Briefly, hypoxic culture conditions (oxygen level Ͻ2%) were achieved with a pouch system providing a CO2-enriched anaerobic environment (BBL GasPak Pouch System, Becton Dickinson) as previously reported (50).…”
Section: Methodsmentioning
confidence: 99%
“…Quantification of cells undergoing apoptotic cell death by flow cytometry analysis was performed as we previously described using the Telford method (41).…”
Section: Methodsmentioning
confidence: 99%
“…p53 has also been shown to play a crucial role in mediating apoptotic cell death in renal ischemia-reperfusion injury (Wada et al 2005;Wada et al 2008), a common cause of acute kidney injury that is characterized by widespread tubular and microvascular apoptosis (Dagher 2004;Hochegger et al 2007;Sutton et al 2008;Singaravelu et al 2009;Molitoris et al 2009). It was suggested that an apoptosisassociated p53 transcriptional target PERP can play a key role in p53-mediated apoptotic pathways (Singaravelu et al 2009).…”
Section: P53 and Pathologies Associated With Acute Ischemiamentioning
confidence: 99%
“…It was suggested that an apoptosisassociated p53 transcriptional target PERP can play a key role in p53-mediated apoptotic pathways (Singaravelu et al 2009). …”
Section: P53 and Pathologies Associated With Acute Ischemiamentioning
confidence: 99%